2009
DOI: 10.1002/ejoc.200900485
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of Modular Amino Acid Derivatives Containing Selenium with Pronounced GPx‐Like Activity

Abstract: New chiral selenide‐ and diselenide amino acid derivatives have been synthesized. By a simple and efficient two‐step route, these new compounds were obtained from inexpensive and commercially available L‐amino acids. The products, with a highly modular character, were obtained in good to excellent yields. Selected examples were also efficiently used as GPx mimics, catalyzing the reduction of H2O2 to water at the expense of PhSH. (© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2009)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…19 It was observed that the influence of the chain length between the diselenide moiety and amino acid residue played a crucial role in modulating the GPx like activity of the tested diselenides. Compounds 18c and 18b derived from L-phenylalanine with a longer chain length, showed better results than PhSe) 2 , while compound 18a, with a shorter chain length, was the least effective catalyst screened.…”
Section: Organoselenium Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 It was observed that the influence of the chain length between the diselenide moiety and amino acid residue played a crucial role in modulating the GPx like activity of the tested diselenides. Compounds 18c and 18b derived from L-phenylalanine with a longer chain length, showed better results than PhSe) 2 , while compound 18a, with a shorter chain length, was the least effective catalyst screened.…”
Section: Organoselenium Compoundsmentioning
confidence: 99%
“…In 2009, Braga et al 19 described the synthesis of compounds 18a-c, a new class of chiral diselenides derived from amino acids. 19 It was observed that the influence of the chain length between the diselenide moiety and amino acid residue played a crucial role in modulating the GPx like activity of the tested diselenides.…”
Section: Organoselenium Compoundsmentioning
confidence: 99%
“…The first synthetic organoselenium compound was ebselen (2‐phenyl‐1,2‐benzisoselenazol‐3‐(2 H )one), which mimics the GPx catalytic activity both in vivo and in vitro . Successively, a number of selenium‐containing small molecules have been developed, either by modifying the basic structure of ebselen or by incorporating some structural features of the native enzyme . Substitution of selenium by tellurium in a series of diarylchalcogenides results in a pronounced increase in antioxidant activity as suggested by several authors …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Successively,anumber of selenium-containing smallm olecules have been developed, eitherb ym odifying the basic structure of ebselen or by incorporating somes tructuralf eatures of the nativee nzyme. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] Substitution of seleniumb yt ellurium in a series of diarylchalcogenides results in ap ronouncedi ncrease in antioxidant activity as suggested by several authors. [21][22][23] Stimulated by the numerous interesting biological activities of the ebselena nd its derivatives, many researchers have associated the presence of chalcogen in the aromatic ring, containing conjugativee lectron-donating substituents (OH, NH 2 , NMe 2 ,N HPh), to the reduction of t 50 values (time required to reducet he thiol concentration by 50 %).…”
Section: Introductionmentioning
confidence: 99%
“…The compound studied on the present work, (S )-dimethyl 2-(3-(phenyltellanyl) propanamido) succinate (TeAsp), is a new telluroamino acid derivative of aspartic acid that was found to be the most potent mimetic of GPx among 20 newly synthesized derivatives (Braga et al 2009; Alberto et al 2009) presenting antioxidant properties in vitro . However, when administered to rodents this compound showed potent genotoxic and mutagenic actions (Meinerz et al 2011).…”
Section: Introductionmentioning
confidence: 99%